Historical persecution reaction complex: exploring a link between racial identity and poor leadership outcomes - Searcy, Yan Dominic; Hines, Resche D. (Journal of Black Studies, 2017)
This original study examines the reluctance of oppressed populations to publicly criticize the recognized performance shortcomings of leaders who are members of their identity group. Using critical race theory (CRT), this article utilizes three case examples of Black American leadership that present evidence of what the authors identify as Historical Persecution Reaction Complex (HPRC). HPRC describes four elemental arguments reflecting an oppressed identity group's attempt to protect itself from perceived further social marginalization, limit the exacerbation of oppression, and to preserve the identity group's leadership gains in the larger society by supporting leadership despite recognized shortcomings in the leadership. Although asserting HPRC operates as a functional reaction to oppression by serving both as an act of cohesion and resistance to oppressive structures, the authors suggest that HPRC is paradoxically detrimental to oppressed identity groups due to maintaining substandard leadership.
Keywords: Black identity; antiracism; dept.hhs; leadership; oppression; racial identity